Relações entre uso de smartphones, regulação emocional e bem-estar - Fortes, Amanda Gomes Ferreira Borges (2020)
Smartphones have become part of people’s lives because they provide access to numerous features. Nowadays, the number of people who have a smartphone is very high in both developed countries (like in the United States, where 76% of the population have a smartphone) and in less developed countries (like in Brazil, where 67% have a smartphone). Given the increasing usage of smartphones, the motivations and the impacts caused by this behavior on well-being have become topics of great research interest. In general, the literature about this topic focuses on the negative implications and potential harm that can be generated by the excessive use of smartphones. Current researches reveal that the implications of smartphone usage may vary depending on the types and reasons of use. In this context, the Uses and Gratifications Theory (UGT) and the Compensatory Internet Use Theory (CIUT) help us to understand this phenomenon by suggesting that people tend to use the smartphones as an attempt to relieve their negative feelings. Since the smartphone has become widely accessible for daily use, it is possible that people use them to regulate their daily feelings. However, research results on smartphone usage behavior, considering emotional regulation and the impact on well-being, seem contradictory. Despite evidences that both are related, the role of the emotional regulation in smartphone use is not clear. The divergences and the scarcity of research on this subject are possibly due to the fact that this phenomenon is extremely complex and current. The present study had the aim to investigate smartphone use through time and types of use, as well as the relationship of this phenomenon with emotional regulation and well-being. This dissertation was divided into two empirical articles. The first article aimed to deepen the comprehension of the habitual use behavior with its numerous functions, exploring possible negative and positive implications. From the identification of five purposes of smartphone usage - communication, entertainment, interaction, practicalities and health - it was possible to approach the relationship between each purpose and the degree of harm associated with the smartphone use, as well as its relationship with the degree of the psychological welfare state of the individual. 857 individuals aged from 18 to 70 years old participated in this study (M=30,55; DP=11,49). The participants were invited to complete the Sociodemographic Data Questionnaire, the Smartphone Use Pattern Questionnaire (created especially for this research), the Smartphone Addiction Inventory (SPAI-BR) and the Psychological Well-being Scale (PWBS). Results show that use for interaction and use for entertainment were negative predictors of psychological well-being, while the use for communication and use for health were positive predictors of psychological well-being. Besides, the use for interaction appeared as a predictor of functional impairment associated with smartphone, while the other use purposes were excluded from the model. In this context, the findings of the present study contribute to the understanding of smartphone use behavior in people’s daily lives, without prioritizing either positive or negative side, thus differing from the “problematic use” studies, prevalent in the current literature. The second article aimed to check whether the emotional regulation moderates the relationship between the time of smartphone use and the degree of harm associated with the usage, as well as between the time of smartphone use and psychological well-being. For that, 308 individuals aged from 18 to 67 (M= 29,72; DP= 11,09) years old completed the real-time measurement of smartphone use, based on a daily average reported by specific application for this purpose. Besides, the participants also completed the Smartphone Use Pattern Questionnaire, the Emotional Regulation Questionnaire (ERQ), the Smartphone Addiction Inventory (SPAI-BR) and the Psychological Well-being Scale (PWBS). Results show that time of use is negatively related to well-being and that cognitive reappraisal has a moderating effect, weakening this relationship. Also, when cognitive reappraisal is associated with the use for communication, it is possible to find a dual moderation model, in which the negative relationship between time of use and well-being becomes even weaker. On the other hand, the duration of usage is positively associated with the harm related to the smartphone use, and emotional suppression has a moderating effect, strengthening this relationship. Additionally, when emotional suppression is associated with the use for entertainment, there is a dual moderation model, in which the relationship between time of use and harm associated with use becomes even stronger. The findings have important clinical contributions, as they revealed that smartphone use may have different implications for mental health, if moderated by strategies of emotion regulation and purposes of use. This study can be considered groundbreaking because it has explored variables related not only to the harm that comes from smartphone use, but also because of its potential to promote well-being. Raising awareness and psychoeducation about the risk and protection factors for well-being and the harm associated with smartphone use seems to be essential to mental health nowadays.